2016
DOI: 10.4102/the.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond counting the numbers: Shifting higher education transformation into curriculum spaces

Abstract: Since the dawn of democracy in South Africa, the path of higher education transformation has been guided by the ‘White Paper 3: A Programme for Higher Education Transformation’. This path has largely been conceptualised within a framework of equity through redress and social justice that sought to change the face of higher education through demographic changes. Hence higher education transformation largely took on a number-counting process. The curriculum changes that have taken place thus far have largely bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Recurrent themes have focused on gender and economic opportunities, social class, race and level of education. For instance, studies from Southern Africa have linked poverty to reported risky sexual behaviours (Wamoyi et al, 2014;Shisana et al, 2009;Madise et al, 2007) such as casual sex (Tadesse & Yakob, 2015;Lyons et al 2015) and transactional sex (Ranganathan et al, 2016;Udingwe et al, 2014). Thus, in the case of transactional sex, the need to survive becomes the motivation behind the sexual activity of adolescent girls.…”
Section: Predictors Of Sexual Behaviours and Educational Attainmentmentioning
confidence: 99%
“…Recurrent themes have focused on gender and economic opportunities, social class, race and level of education. For instance, studies from Southern Africa have linked poverty to reported risky sexual behaviours (Wamoyi et al, 2014;Shisana et al, 2009;Madise et al, 2007) such as casual sex (Tadesse & Yakob, 2015;Lyons et al 2015) and transactional sex (Ranganathan et al, 2016;Udingwe et al, 2014). Thus, in the case of transactional sex, the need to survive becomes the motivation behind the sexual activity of adolescent girls.…”
Section: Predictors Of Sexual Behaviours and Educational Attainmentmentioning
confidence: 99%
“…Many policy changes underpinned by these imperatives were consequently implemented since 1994, thus ensuring that university enrolment of students from previously disadvantaged population groups substantially increased, as did enrolment figures in general (Badat 2007). However, the transformation agenda has, to date, been largely limited to improved institutional access and number counting (Ramrathan 2016), as well as the implementation of a variety of foundational programmes. Of particular concern however, is the fact that while university participation rates have increased, university completion rates remain untenably low, especially with regard to students from previously disadvantaged backgrounds (Council on Higher Education 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These three universities amongst other things see transformation in the light of numbers; UCT's four key indicators of transformation have three focuses: on numbers and diversity which in effect caters for the same thing because racial diversity can only be effectively expressed in numbers. Ramrathan (2016) argues that higher education transformation in South Africa has primarily focused on the domain of counting numbers and this stems from the transformation agenda for higher education, which set several goals that were mostly numerical changes. Although universities have been taking steps to address these numerical imbalances (as seen from their understanding of transformation), problems of throughput, dropout and academic support remain.…”
Section: Why Has There Been Little or No Transformation?mentioning
confidence: 99%